Congratulation of Prezident of Lithuanian Nurses ’Managers’ Union - dr. Daiva Zagurskienė, Prezident of Lithuanian Nurses 'Managers' Union (Slauga. Mokslas ir praktika, 2020)
Congratulation of Prezident of Lithuanian Nurses ’Managers’ Union.